2012
DOI: 10.1097/nhh.0b013e318252c3d5
|View full text |Cite
|
Sign up to set email alerts
|

Take the Challenge

Abstract: Parents of children with chronic illnesses experience tremendous burden when caring for their children at home. There are many challenges that are present throughout the course of chronic illnesses. To provide better care to the family caring for an ill child at home, clinicians must understand the experiences family members go through on a daily basis. The purpose of this article is to help clinicians better understand these parental experiences; by increasing clinicians' awareness, strategies can then be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…For more background information and strategies to improve support for parents of chronically ill children, see e.g. Newton and Lemarche [71]. Quality of life assessment and the evaluation of disease burden in family members of AADCD patients are an essential part of the ongoing iNTD registry study [9].…”
Section: Part V: Social Issues and Transitionmentioning
confidence: 99%
“…For more background information and strategies to improve support for parents of chronically ill children, see e.g. Newton and Lemarche [71]. Quality of life assessment and the evaluation of disease burden in family members of AADCD patients are an essential part of the ongoing iNTD registry study [9].…”
Section: Part V: Social Issues and Transitionmentioning
confidence: 99%
“…Hence, parenting a child with a longstanding illness is reported to be challenging because of illness-specific demands [29][30][31]. Investigating the role played by the parents of chronically ill children in their children's development and trying to define the aim of training programs for parents of chronically ill children (research question 2), we revealed that:…”
Section: Literature Review Resultsmentioning
confidence: 99%